INFLUENCE OF CUSTOMER FOCUS ON COMPETITIVENESS OF FOOD AND BEVERAGE MANUFACTURING FIRMS IN KENYA - Muiruri , Edward Maina; Ngugi, Dr. Patrick Karanja; Kihara, Dr. Allan (European Journal of Business and Strategic Management, 2021)
Purpose: Manufacturing firms are critical to the economic growth and development through provision of products and employment. Their competitiveness is therefore critical. The firms have been facing steep competition from foreign companies due to increased globalization. Strategic drivers have been found to be key enablers of firm competitiveness and performance. It is on this basis that the study sought to establish the influence customer focus on the competitiveness of food and beverage processing companies in Kenya. Methodology: The study was informed by commitment trust theory. Empirical studies were reviewed to provide the basis for research gaps to be filled by the current study. Descriptive research design was employed while the target population was the 187 food and beverage processing firms in Kenya. A census was used where all the 187 companies were contacted. Structured questionnaire was used to obtain the primary data which was analyzed through mixed method analysis. Descriptive statistics were used to analyze quantitative data while qualitative data was analyzed through content analysis. Inferential statistics were used to analyze the relationship between variables through the regression model. The findings were presented in form of tables, pie-charts and bar-graphs. Findings: It was established that customer focus was upheld in most of the surveyed food and beverage processing companies where after sale services, customer engagement and customer contacting were the main platforms applied. It was concluded that while most of the food and beverage processing firms recognized key strategic drivers (customer focus) as a major aspects of competitiveness, most of the firms did not practically embrace the drivers which could explain their continued lack of competitiveness. Unique contribution to theory, practice and policy: The study recommended that for the food and beverage processing companies to take their place in the local and global market, the management should embrace and keenly focus on customer focus.